ANALYSIS OF TAX MANAGEMENT OF THE BALANCE IN FAVOR OF THE EXPORTER AND ITS INFLUENCE ON FINANCIAL MANAGEMENT IN THE PERUVIAN CONTEXT - Canales Baldarrago, Nataly (2025)
Objective: To analyze the tax management of the exporter’s credit balance, evaluating its influence on financial management in Peruvian exporting companies. Method: A quantitative research approach was adopted, with theoretical-explanatory analysis, a non-xperimental design, and a descriptive level in the analysis of tax management in the Peruvian context. The data compiled are from official sources provided by SUNAT. Results: We have a positive trend in the credit balance, which indicates an increase in tax benefits for exporting companies in recent periods, influencing having resources to invest or ake asset purchases according to their financial planning. < The quantitative analysis shows that exports in 2022 reached US $ 63,193 million, reflecting an increase of 3.7% compared to 2021, providing them with greater flexibility to operate, invest, and cover costs. Efficient management of this  balance optimizes financial resources and reduces dependence on external financing. Discussion: Therefore, tax management significantly influences financial management. This balance can be considered a tax credit that companies can claim as a refund or use to offset future tax obligations. This, in turn, can significantly influence companies’ liquidity and financial strategy. Conclusion: In summary, the results obtained regarding the variables analyzed show that from 2020 to date, approximately 6,800 exporters throughout Peru have requested the refund of this balance benefit. Of this group, more than 3,500 have opted for the account credit option, thus achieving a positive impact